The research of pharmacokinetic parameters and metabolism of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate for use in military and civilian medicine - Usenko, D. L.; Varynskyi, B. O.; Kaplaushenko, A. G.; Safonov, A .A.; Panasenko, O. I.; Morozova, L. P.; Shmatenko, O. P.; Solomennyi, А. М.; Усенко, Д. Л.; Варинський, Борис Олександрович; Каплаушенко, Андрій Григорович; Сафонов, Андрій Андрійович; et al. (My University, 2024)
Introduction. Chromatographic methods are often used in the study of pharmacokinetic parameters. Thus, the aim of the study was to investigate the pharmacokinetic parameters and metabolism of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate (ASP) as a potential active pharmaceutical ingredient with high rates of proven acto- and stress-protective effects, which can be recommended for use in military and civilian medicine. The aim of the study is to investigate the pharmacokinetic parameters and metabolism of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate (ASP) in the blood serum of rats by intragastric administration. Materials and methods. Blood sampling of experimental animals was carried out within 24 hours with intervals of 0.25, 0.75, 2.5, 7.5, 13.5 and 24 hours. Approval of the ethics committee № 6 of 08.06.2021. The obtained plasma was used to determine the concentration of ASP (chromatographically) and identify possible metabolites (mass spectrometrically). To evaluate the pharmacokinetic properties of ASP, the following data were calculated: area under the pharmacokinetic curve "concentration-time" (AUC), total clearance (cl), the constant elimination (Kel), volume (Vd), period elimination half-life (T1/2). Results. The analysis of the main pharmacokinetic parameters of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate (ASP) by intragastric introduction to rats was held. For oral use AUC is 3.7088 μgh/ml. The half-life (T1/2) is 6.06 hours. The following possible metabolic products were predicted for phase II biotransformation. This is a reaction of O-glucuronation of an aliphatic acid, formation of a thioester through S-methylation, and possible formation of a glycine conjugate. And also carnitine conjugation (based on a collection of enzymes). Analysis of the pseudomolecular ion peak shows the possible formation of a glycine conjugate corresponding to the structure predicted in BioTransformer. The presence of O-glucuronide as a metabolite was confirmed by PLS DA VIP score and t-test analysis. Conclusions. As a result, the main pharmacokinetic parameters (AUC, cl, Kel, Vd, T1/2) and metabolism (formation of thioether, formation of conjugate of glycine and O-glucuronide) of sodium 2-((4-amino-5-(thiophene)-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate (ASP) in the blood serum of rats was studied. Вступ. При дослідженні фармакокінетичних параметрів часто використовують хроматографічні методи. Таким чином, метою роботи було дослідження фармакокінетичних параметрів та метаболізму натрію 2-((4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-іл)тіо)ацетату (ASP), як потенційного активного фармацевтичного інгредієнту з високими показниками доведеної акто- та стреспротекторної дії, що може бути рекомендованим для застосування у військовій та цивільній медицині. Метою дослідження є вивчення фармакокінетичних параметрів і метаболізму натрію 2-((4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-іл)тіо)ацетату (ASP) у сироватці крові щурів шляхом інтрагастрального введення. Матеріали і методи. Забір крові піддослідних тварин проводили протягом 24 годин з інтервалами 0,25, 0,75, 2,5, 7,5, 13,5 і 24 години. Отриману плазму використовували для визначення концентрації ASP (хроматографічно) та ідентифікації можливих метаболітів (мас-спектрометрично). Для оцінки фармакокінетичних властивостей ASP були розраховані такі дані: площа під фармакокінетичною кривою «концентрація-час» (AUC), загальний кліренс (cl), постійна елімінація (Kel), об’єм (Vd), період піввиведення (T1/2). Результати. Проведено аналіз основних фармакокінетичних параметрів (ASP) при внутрішньошлунковому введенні щурам. Рішення комісії з біоетики № 6 від 08.06.2021. Для перорального застосування AUC становить 3,7088 мкг/мл. Період напіввиведення (T1/2) становить 6,06 години. Наступні можливі метаболічні продукти були передбачені для фази II біотрансформації. Це реакція О-глюкуронування аліфатичної кислоти, утворення тіоефіру через S-метилювання та можливе утворення кон’югату гліцину. А також кон'югація карнітину (на основі набору ферментів). Висновки. В результаті роботи було досліджено основні фармакокінетичні параметри (AUC, cl, Kel, Vd, T1/2) та метаболізм (утворення тіоефіру, утворення кон’югату гліцину та О-глюкуроніду) натрію 2-((4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-іл)тіо)ацетату (ASP) у сироватці крові щурів.
Дослідження фармакокінетичних параметрів та метаболізму натрію 2-((4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-іл)тіо)ацетату для застосування у військовій та цивільній медицині
Keywords: 1,2,4-triazole; HPLC-MS; metabolism; biotransformation prediction; 1,2,4-триазол; ВЕРХ-МС; метаболізм; прогноз біотрансформації